Examining Value Co-Creation as Moderator in Brand Image and Loyalty Relationship in Halal Cosmetics - conny; Juharsah; Dzulfikri Azis Muthalib; Harmiaty Bahar (LP2M IAIN Palopo, 2026)
This study examines the influence of customer experience and value co-creation on customer loyalty, with brand image as a mediating and moderating variable. It hypothesizes that both factors positively affect loyalty directly and indirectly through brand image. Methods: A quantitative survey was conducted with 350 Wardah cosmetic users selected through purposive sampling. Data were collected via an online questionnaire using a 5-point Likert scale. Variables include customer experience, value co-creation, brand image, and customer loyalty. Data were analyzed using PLS-SEM with SmartPLS. Results: Findings show that customer experience significantly influences brand image, and brand image significantly affects customer loyalty. Value co-creation also has a direct positive effect on customer loyalty. Brand image mediates the relationship between customer experience and customer loyalty and moderates the effect of value co-creation on customer loyalty by strengthening it. ImplicationsCompanies should enhance customer experience and promote value co-creation to strengthen brand image and loyalty. Future research should apply longitudinal designs and include additional variables to improve generalizability and deepen insights into customer behavior dynamics